Dietary habit and lifestyle patterns: a predisposing factor of cardiovascular diseases among university lecturers in Ibadan (2011)
Dietary habits and lifestyle patterns have all been confirmed to be predictors of cardiovascular diseases among adults. Basic descriptive data on dietary habits and lifestyle patterns are however lacking for university lectures in Ibadan. This study was carried out to determine the lifestyle patterns that could predispose university of Ibadan lectures to cardiovascular diseases. Two hundred lectures were purposively selected and the descriptive survey research design was used for the study. The data collected were analysed with the descriptive statistics of frequencies and percentages. Results showed that dietary habits and lack of exercise were significant predisposing factors of cardiovascular diseases among University of Ibadan lecturers. It was concluded that the lectures life style patterns may be damaging to their heart. It was recommended that health and fitness awareness programmes that will encourage daily healthy living and the use of sporting facilities on campus should be organized by the Department of Human Kinetics and Health Education for all lectures in the University of Ibadan.